Kapitalisme, Mikonka, dan Kerentanan Human Security di Jepang - Ahmad Majdi; Imam Fadhil Nugraha (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the phenomenon of “mikonka”—the rising trend of remaining unmarried among the Japanese population—through the lens of human security, positioning capitalism not as the sole cause but as an enabling structure that reshapes the conditions under which individuals make decisions regarding marriage. This study will employ a qualitative approach with a descriptive-analytical design and a single case study of Japan as the primary unit of analysis, covering the time period from the 1990s to the 2020s. The data used were collected through document analysis of academic literature, official government publications, and reports from international institutions, and analyzed using an emancipatory human security framework combined with the protection-empowerment pillars of CHS 2003, Giddens’ structuration theory, and the concept of enabling structures at four levels: material, normative, ideological, and institutional. The findings indicate that capitalism transforms marriage from a social norm into a high-risk economic project through the precariousness of work, while simultaneously commodifying relational needs through alternative markets, as empirically evidenced by the solo economy projected to exceed 100 trillion yen and the AI companion market reaching 2,167.6 million USD by 2025. This study also finds that mikonka produces slow violence against human security across three dimensions: living insecurity that threatens economic security, kodokushi as a systemic indicator of weakened personal security, and atomization that erodes community security. Projectively, the state’s regulatory response has proven inadequate because it operates at the level of individual incentives without addressing structural roots, as evidenced by the decline in Japan’s TFR amidst the most expansive family policies in East Asia.